(untitled) (Physical Education, Health and Social Sciences, 2025)
This study investigates the pragmatic features of internet memes used in representation of different Pakistani major political parties on social media. Language is traversed with opportunities to negotiate meaning. The study delves into pragmatic strategies in meme captions, including implicature, speech acts, presupposition, and politeness strategies. We selected four political internet memes (2020–2022) from social media platforms including Facebook and Twitter. The analysis illustrates the ways in which pragmatic devices employed in memes, including the use of indirect speech acts, satire, irony, and presupposition, influence political discourse. The study concludes that meme captions are functionalized mainly by brevity, implicit meaning, humor and humor-based pragmatics, and by puns and sarcasm, in order to criticize political figures and events. The results indicate memes act as an effective tool of ideological positioning and persuasion to the public. Future studies could have multimodal dimensions, which will also include visual influences (color, font, and imagery), contributing to a broader understanding of political discourse in the context of Pakistani internet memes.